Proceso de atención de enfermería en paciente masculino de 60 años con Sars Cov 2 - Bosquez Silva, Johanna Lucia (2020)
According to the WHO, coronaviruses are a broad family of viruses producing clinical pictures that range from the common cold to more serious diseases, such as the coronavirus that caused severe acute respiratory syndrome (SARS-CoV2). It is a new type of coronavirus that can affect people by infecting the upper and lower respiratory tract and was first detected in December 2019 in Wuhan city, Hubei province, China. There are still many questions that are unknown in relation to the disease that COVID-19 produces. Serious complications include, in addition to respiratory disease that can lead to respiratory failure, such as myocarditis, bleeding disorders including pulmonary thromboembolism. Next, I will present in the academic work of this clinical case before this infection a correct process of nursing care in a 60-year-old male patient with SARS CoV 2.